Indigenous knowledge and practices of the Iraynon in Barangay San Agustin, Valderama, Antique in disaster risk reduction and management. - Rivera, Dannah Karoline N.
This study describes the indigenous knowledge and practices of the Iraynon-Bukidnon in San Agustin, Valderrama, Antique in terms of disaster risk reduction and management. Primary data were collected through focus group discussions (FGD) with the Iraynon-Bukidnon men and women participants; key informant interviews with the Iraynon-Bukidnon Elders, and interview of a Municipal Disaster Risk Reduction Officer. Secondary data were collected from the review of related literature regarding indigenous peoples, their indigenous knowledge and practices in terms of disasters, and the role of the leaders or Elders in indigenous communities. These collected data were interpreted using the theoretical model of this study which was Baumwoll?s categorization of indigenous knowledge namely: ecological knowledge, cultural tradition, environmental ethic, and connection to place. This study highlighted the importance of indigenous knowledge for disaster risk reduction due to indigenous people?s worldview that land is sacred, land is life, which has greatly helped the community?s resilience towards natural disasters. This study revealed the Iraynon-Bukidnon as placing high value and positive image on their knowledge and practices which were grounded in a long tradition of coping with disasters. Their strategies to cope with these disasters are fastened in their daily lives rather than extraordinary measures to face extreme natural events. This study also verified the importance of indigenous leadership in fostering indigenous knowledge and practices since the elders are the main knowledge carriers and cultural bearers. This study provided important information regarding the Iraynon-Bukidnon, which could contribute to the overall Philippine literature on indigenous knowledge and practices on disaster risk-reduction and management.